2017
DOI: 10.1080/03007995.2017.1333953
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent thoracic cancers among patients diagnosed with lung cancer: a SEER database analysis

Abstract: There is an excess risk for the development of esophageal cancer and second primary lung cancer following an initial lung cancer diagnosis. This risk is present irrespective of gender or receipt of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 12 publications
3
27
1
Order By: Relevance
“…In contrast, patients with lung HGNEC had elevated risks of getting leukemia and cancers of the oral cavity and pharynx, colon and rectum, esophagus, pancreas, urinary bladder, kidney and renal pelvis, and lung and bronchus. Cancer risk reduction in these patients is consistent with prior researches, which are relevant to lung cancer and non-small cell lung cancer [11,12]. Although the causes of risk reduction are not well understood, they may be associated with patient age at diagnosis of SCLC.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, patients with lung HGNEC had elevated risks of getting leukemia and cancers of the oral cavity and pharynx, colon and rectum, esophagus, pancreas, urinary bladder, kidney and renal pelvis, and lung and bronchus. Cancer risk reduction in these patients is consistent with prior researches, which are relevant to lung cancer and non-small cell lung cancer [11,12]. Although the causes of risk reduction are not well understood, they may be associated with patient age at diagnosis of SCLC.…”
Section: Discussionsupporting
confidence: 89%
“…focused on early(I/II) lung cancer patients with radiotherapy alone. The present studies demonstrated that early lung cancer patients harbored higher risk of metachronous SPLC compared with advanced lung cancer patients because the longer survival time after successful treatment of lung cancer gave such patients more chance for development of metachronous SPLC 24,25 . Our study also confirmed that the IPLC patients IPLC at stage I with 0.98% per year were associated with a highest risk of developing metachronous SPLC than those in the advanced stage groups.…”
Section: Discussionmentioning
confidence: 60%
“…However, our study suggested that the risk of developing metachronous SPLC for IPLC patients with radiotherapy was lower compared with that of patients without radiotherapy in the first 5 years follow-up period, which was consistent with the study of Abdel-Rahman et al . 25 . Even when we adjusted various factors of metachronous SPLC through propensity score matching analysis, this decreased risk of metachronous SPLC in the radiotherapy group still remained.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, the incidence of SPC after NSCLC was lower than Hayat et al, and the probable reason might be because we excluded patients with history of malignant disease. The highest morbidity of SPCs after the diagnosis of NSCLC was lung cancer (45.1%), which might be due to the risk factors that cause lung cancer still exist (15). The second most common SPC was prostate cancer followed by colon and rectum cancer, which was similar to the incidence of these cancers in the general population (1).…”
Section: Discussionmentioning
confidence: 69%